2011
DOI: 10.1007/s11102-011-0335-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of octreotide LAR and lanreotide autogel as post-operative medical treatment in acromegaly

Abstract: Long-acting somatostatin analogs are frequently used as adjuvant treatment of acromegaly patients after noncurative surgery. This sudy aims to compare the efficacy of octreotide long-acting release (OCT) and lanreotide Autogel (LAN) in acromegaly patients. Sixty-eight patients not cured by transsphenoidal endoscopic or microscopic pituitary surgery between 2003 and 2009 were retrospectively analyzed (25 men; 43 women; mean age 41.1 ± 10.9 years [range 18–65 years]). The patients were assigned randomly to OCT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 38 publications
2
31
0
2
Order By: Relevance
“…Patients were randomly assigned and equally distributed into 60-mg, 90-mg, or 120-mg dosing groups. Treatment was administered deep subcutaneously in the buttocks at Weeks 0, 8,12,16, and 20 using the injection device available at the time of the study, which comprised a ready-to-use, prefilled syringe with either a 1.2-mm (60-mg and 90-mg doses) or 1.4-mm diameter needle (120-mg doses).…”
Section: Phase II Dose-response Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were randomly assigned and equally distributed into 60-mg, 90-mg, or 120-mg dosing groups. Treatment was administered deep subcutaneously in the buttocks at Weeks 0, 8,12,16, and 20 using the injection device available at the time of the study, which comprised a ready-to-use, prefilled syringe with either a 1.2-mm (60-mg and 90-mg doses) or 1.4-mm diameter needle (120-mg doses).…”
Section: Phase II Dose-response Studymentioning
confidence: 99%
“…The drug is slowly released over a period of at least 1 month following administration from a depot formed at the injection site [8]. In international studies, this treatment has demonstrated good efficacy and safety in the medical management of acromegaly [9-13], with an efficacy and safety profile that is similar to that of octreotide LAR [14][15][16]. Lanreotide Autogel has been used for a number of years in clinics around the world.…”
Section: Phase II Dose-response Studymentioning
confidence: 99%
“…But, there is limited published literature with new criteria for acromegaly on outcomes and factors affecting the remission rates. Patients for which biochemical remission is not achieved with initial resection are left with few options; reoperation, medical therapy and radiosurgery (32,36). Medical management and radiosurgery are costly and variably effective options.…”
Section: Introductionmentioning
confidence: 99%
“…Somatostatin analogs exert their maximum effect on GH levels after 3-6 months, 33 and on IGF-1 levels by 6-12 months. 34 Attempts have been made to identify patients who will exhibit a good response to somatostatin analogs. For example, it has previously been demonstrated that so-called "densely granulated" somatotroph adenomas are more likely to respond to somatostatin analogs than sparsely granulated adenomas, with long-term IGF-1 normalization rates of 52% versus 7%, respectively.…”
Section: Medical Therapy: Monotherapy Somatostatin Analogsmentioning
confidence: 99%
“…Interestingly, using the OGTT GH cutoff of ,0.4 µg/L, biochemical control with either agent decreased substantially to 27% for octreotide LAR and 31% for lanreotide ATG. 34 Notably, there was no crossover between drugs in this study, and patients who required additional therapy including a second surgery within 18 months were excluded from the final analysis.…”
Section: Adjuvant (Postsurgical) Therapymentioning
confidence: 99%